2014
DOI: 10.2174/1568026614666140827144752
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent Ligands Targeting Chemokine Receptor Dimerization: Molecular Design and Functional Studies

Abstract: Increasing evidence has shown that chemokine receptors may form functional dimers with unique pharmacological profiles. A common practice to characterize such G protein-coupled receptor dimerization processes is to apply bivalent ligands as chemical probes which can interact with both receptors simultaneously. Currently, two chemokine receptor dimers have been studied by applying bivalent compounds: the CXCR4-CXCR4 homodimer and the CCR5-MOR heterodimer. These bivalent compounds have revealed how dimerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…More data are nonetheless required to determine whether there are common residues and/or structural determinants involved in chemokine receptor dimerization, if each receptor bears an individual dimerization signature or even if the residues involved in homodimers are the same that those forming heterodimers. In addition to the CKR themselves, studies that target dimerization with bivalent ligands reinforce the idea that receptor dimerization is essential to understand chemokine biology …”
Section: Chemokine Receptor Dimerization/oligomerization: a Potentialmentioning
confidence: 95%
See 1 more Smart Citation
“…More data are nonetheless required to determine whether there are common residues and/or structural determinants involved in chemokine receptor dimerization, if each receptor bears an individual dimerization signature or even if the residues involved in homodimers are the same that those forming heterodimers. In addition to the CKR themselves, studies that target dimerization with bivalent ligands reinforce the idea that receptor dimerization is essential to understand chemokine biology …”
Section: Chemokine Receptor Dimerization/oligomerization: a Potentialmentioning
confidence: 95%
“…In addition to the CKR themselves, studies that target dimerization with bivalent ligands reinforce the idea that receptor dimerization is essential to understand chemokine biology. 67 Many authors [68][69][70][71][72][73][74][75] have shown the impact of chemokine receptor complexes (dimers/oligomers) on chemokine functions (Table 1).…”
Section: Chemokine Receptor Dimerization/oligomerization: a Potentialmentioning
confidence: 99%
“…Improvement of chemokine‐derived short peptide affinity and potency by dimerization via a disulfide bridge at the first cysteine residues has previously been reported and suggested to be due, at least in part, to a mimicry effect of the first disulfide bridge present in the parental chemokines . Surprisingly, in the current study, dimerization of Mimokine SR (D) with C terminal cysteine or lysine linkers enhanced to the same extent the peptide interaction with CXCR4, suggesting that other effects might also be involved.…”
Section: Discussionmentioning
confidence: 83%
“…26 The first bivalent ligand (designated as compound 1b , Figure 1) was designed with an overall length of 21 atoms based upon previous bivalent ligand reports involving the MOR, 23 along with two control compounds with the same length of spacer (compound 2b for monovalent control attaching maraviroc, compound 3b for monovalent control attaching naltrexone). In order to study how linker length affects activity, the overall length was decreased or increased by two atoms in compounds 1a or 1c respectively.…”
Section: Resultsmentioning
confidence: 99%